Attitudes of Nursing Students Related the Registration and Preservation of Personal Health Data of Patients - Sevgi Pakiş Çetin; Kıvan Çelik (Dokuz Eylul University, 2021)
Background: Preservation of personal health data is directly related to the right to live. However, it is very difficult to ensure patient privacy nowadays. Objectives: This research was conducted to determine the attitudes of nursing students towards the registration and preservation of patients' personal health data. Methods: The research is a descriptive cross-sectional study with 454 students registered in the Faculty of Health Sciences Nursing Department of a university in the fall semester of the 2019-2020 academic year. Data were collected using the "Student Identification Form" and "Registration and Preservation of the Personal Health Data Attitude Scale For Nursing Students". The data were evaluated by the Mann Whitney U test and Kruskal Wallis test. The descriptive features were given as mean, percentages. Results: The mean total score of the "Registration and Preservation of the Personal Health Data Attitude Scale For Nursing Students" was found to be 4.06±0.51. In the scale consisting of five sub-dimensions, it was found that the students obtained the highest score from the "Personal Health Data Information" sub-dimension with the mean score 4.11±0.58; 4.09±0.59 scores from the "Legal Information" sub-dimension, 3.97±0.60 scores from the "Legal Data Sharing" sub-dimension; 3.96±0.61 scores from the "Personal Health Data Sharing" sub-dimension; 4.09±0.63 scores from the "Personal Health Data Registration" sub-dimension. In the study, Cronbach alpha value of the scale was found to be .91. Conclusion: According to the results of the research, it was found that nursing students' attitudes towards registering and preserving personal data were positive and their awareness was high.